P189 Delays in doctor-led arterial blood gases may impact timely implementation and optimisation of acute non-invasive ventilation (NIV). (12th November 2019) - Tang, I; Talwar, A; Manalac, R; Dawson, K; Lightowler, J; Petousi, N; Nickol, AH
Abstract : Introduction: Timely NIV reduces mortality from 20 to 10% in acute hypercapnic COPD [Plant 2000], however successive BTS audits show a much higher mortality rate. The 2017 NCEPOD Review demonstrated a number of shortfalls in current practice across the UK, including delays in initiating NIV in ¼ patients, and oxygen toxicity in 1/5 patients. Delays in recognition of hypercapnia may contribute to this. The BTS Standard of care is to deliver acute NIV within 120 minutes of arrival in hospital, and within 60 minutes of a blood gas for all patient fulfilling criteria for acute NIV, and for a blood gas to be carried out within 120 minutes of NIV initiation. Methods: We audited timing of arterial blood gases in all patients identified from the Electronic Patient Record as having an episode of acute hypercapnic ventilatory failure requiring NIV admitted to our trust between 1st Oct–30th Nov 2018. Results: 30 patient-encounters were identified, comprising 28 patients (age 72.2±7.8 years; 17 female). 21 patients had COPD; other diagnoses were obesity/OSA, heart failure, CF, bronchiectasis and pneumonia. The ceiling of care was documented for all patients, being NIV in 27 patients and consideration of intubation in one. Discussion: Delays in blood gases are common in our organisation, potentially impacting adversely on timely clinical decision making. Arterial blood gases are carried out by junior doctors, with the majority of patients being admitted out of hours when the work-force is lowest. We propose implementing nurse-led capillary blood gas sampling in our EAU. Capillary blood gas sampling is already successfully in use first-line on our Respiratory ward, and in our Sleep and Ventilation outpatient service. It is generally preferred by patients, and accurate in skilled hands. Furthermore nursing-numbers have greater stability in- and out- of hours. Training has been initiated, and practice will be re-audited in due course.